Luck, value, and commitment themes from the ethics of Bernard Williams - Heuer, Ulrike; Lang, Gerald (Oxford : Oxford University Press, 2012)
This collection comprises 11 essays which engage with, or take their point of departure from, the influential work in moral and political philosophy of Bernard Williams (1929-2003). Leading philosophers explore Williams's work on systematic moral theory moral luck, 'internalism', epistemology and intuitionism, and equality.
Description based on online resource; title from home page (viewed on July 12, 2012).
Includes bibliographical references and index.
Keywords: Williams, Bernard Arthur Owen; Ethics